2009
DOI: 10.1111/j.1440-1827.2009.02459.x
|View full text |Cite
|
Sign up to set email alerts
|

Pleural malignant mesothelioma with invasive micropapillary component and its association with pulmonary metastasis

Abstract: The micropapillary pattern (characterized by papillary structure with tufts lacking a central fibrovascular core) is a predictor of aggressive carcinoma. The purpose of the present study was to review 34 pleural malignant mesotheliomas (21 epithelioid, five sarcomatoid, seven biphasic and one lymphohistiocytoid), with special reference to the presence of invasive micropapillary component. Two invasive micropapillary pattern-positive tumors were identified. The invasive micropapillary pattern was seen to have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…It is rarely reported in DMPM. 21,36 Mogi et al 21 reported a micropapillary component in 2 of 34 DMPM (5.9%), and these cases showed significantly more lymphatic invasion, pulmonary metastasis, and a trend toward more lymph node involvement compared with those without a micropapillary component. In our series, 20 cases (9%) out of 232 patients with epithelioid DMPM were micropapillary predominant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is rarely reported in DMPM. 21,36 Mogi et al 21 reported a micropapillary component in 2 of 34 DMPM (5.9%), and these cases showed significantly more lymphatic invasion, pulmonary metastasis, and a trend toward more lymph node involvement compared with those without a micropapillary component. In our series, 20 cases (9%) out of 232 patients with epithelioid DMPM were micropapillary predominant.…”
Section: Discussionmentioning
confidence: 99%
“…The micropapillary pattern was defined as papillary structures with tufts lacking a central fibrovascular core (Figure 1C). 11,21 The solid pattern consists of sheets or nests of polygonal to round tumor cells, lacking any specific morphologic arrangement or pleomorphism (Figure 1D). 1,6 Tumors with anaplastic or prominent giant cells were designated as pleomorphic features (Figure 1E).…”
Section: Histologic Evaluationmentioning
confidence: 99%
“…However, clinical, radiological, histological, and ultrastructural features along with D2-40, HBME-1, and WT-1 expression were definitive for a diagnosis of mesothelioma. A micropapillary pattern in mesothelioma has been rarely reported [ 2 ], but, when present, this growth pattern shows poor prognosis with aggressive lymphatic invasion and lymph node metastasis. In a previous study of small cell mesothelioma, tumor cells showed immunoreactivity for neuron-specific enolase and cytokeratin, but not for chromogranin A and CEA [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pleural mesothelioma is a rare neoplasm and roughly 70% are the epithelioid type, which is characterized by proliferation of epithelioid tumor cells with a tubulopapillary growth pattern [ 1 ]. There have been few reports of mesothelioma having a micropapillary pattern [ 2 ] and a small cell component [ 3 ]. To the best of our knowledge, there has been no previously reported case containing both micropapillary and small cell components.…”
mentioning
confidence: 99%
“…31 Of note, a micropapillary pattern (without central fibrovascular core) should be classified as something other than tubulopapillary because a micropapillary pattern correlates with a higher incidence of lymphatic invasion. 32 In addition, tubulopapillary epithelioid mesotheliomas require distinction from well-differentiated papillary mesotheliomas (WDPMs), which are classified as a separate subtype in the 2015 World Health Organization classification, 24 although WDPMs can (rarely) show invasive foci. 33 Recently, epithelioid mesotheliomas with marked nuclear pleomorphism in more than 10% of the tumor have been shown to behave like sarcomatoid and biphasic variants, with a proposal that a ''pleomorphic'' MM variant be recognized as an adversely prognostic epithelioid pattern.…”
Section: Cytological Diagnosis Of MMmentioning
confidence: 99%